Effects of Presowing Treatment on Germination and Seedling Vigour in Dioscorea deltoidea - ANJU S. THAKUR; P.S. THAKUR (Seed Research, 2026)
Dioscorea deltoidea, an endangered medicinal perennial climber is recommended for propagation by seeds to save the medicinally rich rhizome. The seeds of this species show poor and erratic germination. Seeds showed photoblastic nature with maximum germination recorded at 25°C. Presowing chilling at 2°C for 60 days resulted in 95 per cent germination, besides registering 5 days early germination. Other treatments like, 2 cycles of wetting and drying, osmoconditioning with -0.8 MPa, permeation with 50 ppm IAA and 100 ppm kinetin to improve seed germination and vigorous seedlings. Hence, presowing treatment of seeds is recommended for enhancing germination and seedling vigour.